Steganography for Data Hiding in Digital Audio Data Using Combined Least Significant Bit and Blowfish Method - Pradana, Rizal; Hallim, Abd; Faldi, Faldi (LPPI Universitas Muhammadiyah Kalimantan Timur (UMKT), 2025)
Abstract – The purpose of this research is to examine the utilization of steganography and Blowfish encryption to maintain message confidentiality in digital audio files. This research combines LSB encryption and Blowfish algorithm, focusing on embedding text into audio, with PSNR analysis. Results show the effectiveness of the method without significantly affecting audio quality, with PSNR values above 50dB. The application of Blowfish and LSB to audio files successfully secures the message, and the use of base64 increases the security level.